Data from: Continent-wide population genomic structure and phylogeography of North America’s most destructive conifer defoliator, the spruce budworm (Choristoneura fumiferana) ... - Lumley, Lisa; Pouliot, Esther; Laroche, Jérôme; Boyle, Brian; Brunet, Bryan; Levesque, Roger; Sperling, Felix; Cusson, Michel (Dryad, 2020)
The spruce budworm, Choristoneura fumiferana, is presumed to be panmictic across vast regions of North America. We examined the extent of panmixia by genotyping 3650 single nucleotide polymorphism (SNP) loci in 1975 individuals from 128 collections across the continent. We found three spatially structured subpopulations: Western (Alaska, Yukon), Central (southeastern Yukon to the Manitoba-Ontario border) and Eastern (Manitoba-Ontario border and Atlantic). Additionally, the most diagnostic genetic differentiation between the Central and Eastern subpopulations was chromosomally restricted to a single block of SNPs that may constitute an island of differentiation within the species. Geographic differentiation in the spruce budworm parallels that of its principal larval host, white spruce, Picea glauca, providing evidence that spruce trees survived in the Beringian refugium through the Last Glacial Maximum and that at least two isolated populations diverged with spruce/fir south of the ice sheets. Gene flow in ...